Semantics, pragmatics, philosophy a journey through meaning - Jaszczolt, Kasia (Cambridge, United Kingdom Cambridge University Press, 2023)
"This book is about meaning - not the meaning of certain concepts such as the meaning of life or the meaning of freedom but about what it means for linguistic expressions to mean something. It is also a book about meaning for humans. The qualification 'human meaning' is not yet common in linguistics book titles but it is increasingly important to add it. We are already experiencing fundamental differences in how, and what kind of, meaning is approached in computational linguistics and computer science in general on the one hand, and in philosophy of language or sociopragmatics on the other"-- Provided by publisher.
Introduction: Meaning: what it is and where to find it -- Word meanings and concepts -- Composing sentence meaning: tools and their purpose -- Operations on sentences -- Inside the sentence -- Conveying information -- Utterance meaning, or what lurks under the surface -- Meaning in service of its makers -- Conclusion: the future of meaning?
Includes bibliographical references.
Keywords: Meaning (Philosophy); Pragmatics; Semantics